Prioritas Nilai-Nilai Pendidikan Karakter dalam Pendidikan Islam bagi Siswa Berkebutuhan Khusus di SMALBN Temanggung - Wawan Gunawan Sihab Wawan; Rhindra Puspitasari; Ridho Muttaqien; Ahmad Aji Pangestu; Husna Nashihin; Eny Rahmawati; Siti Qomala Hayati (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to analyze the priority character education values implemented in Islamic Religious Education (IRE) for students with intellectual disabilities at SMALBN Temanggung. Character education in inclusive education contexts plays a strategic role, as students with special needs require concrete, contextual, and continuous approaches. This research employs a qualitative descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving Islamic Religious Education teachers, students with intellectual disabilities, and school administrators. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation and member checking. The findings reveal that the priority character education value at SMALBN Temanggung is anti-corruption education, implemented through the internalization of honesty, responsibility, discipline, and trustworthiness. (Lickona, 2013; Zubaedi, 2011). These values are integrated into Islamic Religious Education learning activities, daily habituation, and a school culture based on integrity. The results indicate that Islamic-based character education can be inclusively implemented for students with intellectual disabilities by adapting instructional methods, learning media, and pedagogical strategies. This study contributes both theoretically and practically to the development of character education within Islamic Religious Education in special schools. (Lickona, 2013; Zubaedi, 2011).